2008
DOI: 10.1007/s00018-008-7526-3
|View full text |Cite
|
Sign up to set email alerts
|

Transient cytoskeletal alterations after SOD1 depletion in neuroblastoma cells

Abstract: We have studied the effects of superoxide production after Cu,Zn superoxide dismutase (SOD1) down-regulation by RNA interference. We demonstrated that SOD1 depletion induced, only in neuroblastoma cells, a decrease in actin and beta-tubulin content and accumulation of neurofilament light chain and Tau proteins. Alterations of cell morphology and the microfilament network were also observed, together with the up-regulation of the Cdk5/p35 pathway, which is involved in the regulation of actin polymerization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Ultimately, the radical chain reactions will be blocked by the antioxidant enzymes superoxide dismutase (SOD) in association with catalase or GPX that determines the complete free radicals scavenging (Winterbourn, 1993). Indeed, we demonstrated that GSH finely compensates the decline of SOD1 activity in: (i) cells expressing less active SOD1 mutant found in familial amyotrophic lateral sclerosis (Ciriolo et al, 2001); (ii) cells in which SOD1 is down-regulated by RNA interference (Aquilano et al, 2006; Vigilanza et al, 2008). In particular, the initial burst of superoxide that cannot be eliminated efficiently due to the inactivity of SOD1 is promptly buffered by the induction of GSH synthesis resulting in protection against oxidative stress and cell death.…”
Section: Gsh and Oxidative Stressmentioning
confidence: 99%
“…Ultimately, the radical chain reactions will be blocked by the antioxidant enzymes superoxide dismutase (SOD) in association with catalase or GPX that determines the complete free radicals scavenging (Winterbourn, 1993). Indeed, we demonstrated that GSH finely compensates the decline of SOD1 activity in: (i) cells expressing less active SOD1 mutant found in familial amyotrophic lateral sclerosis (Ciriolo et al, 2001); (ii) cells in which SOD1 is down-regulated by RNA interference (Aquilano et al, 2006; Vigilanza et al, 2008). In particular, the initial burst of superoxide that cannot be eliminated efficiently due to the inactivity of SOD1 is promptly buffered by the induction of GSH synthesis resulting in protection against oxidative stress and cell death.…”
Section: Gsh and Oxidative Stressmentioning
confidence: 99%
“…Earlier studies have revealed that SOD1 is involved in the regulation of cellular cytoskeleton and siRNA-mediated depletion of SOD1 caused alterations in actin cytoskeleton in neuroblastoma cell lines [41]. As a compensatory measure, activation of the p38 MAPK pathway was observed.…”
Section: Resultsmentioning
confidence: 95%
“…It was reported that in neuroblastoma cell lines, depletion of SOD1 caused early cytoskeletal alterations in the cells that ultimately activates pro-survival pathways [41]. The report shows that activation of Hsp27 occurs via the p38 MAPK cascade and that this activation is crucial to the survival of the cell.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, we have showed that the decline of glutathione (GSH), the most abundant nonenzymatic thiol antioxidant, is the primary cause of endogenous NO neurotoxicity, that is, characterized by a prominent protein damage via S-nitrosylation and nitration [13, 17]. In line with this evidence, also the decrease of enzymatic antioxidant for example, SOD1, result in a ROS-mediated damaging effect on cellular targets including mitochondria specifically in cells of neuronal origin [18, 19]. Therefore, the decline of antioxidant levels, generally occurring during physiological ageing, may be likely considered a key factor triggering NO/ROS-mediated neuronal death in ageing and neurodegenerative-related diseases.…”
Section: Introductionmentioning
confidence: 99%